Methicillin-Resistant Staphylococcus aureus ST80 Induce Lower Cytokine Production by Monocytes as Compared to Other Sequence Types - Kolonitsiou, Fevronia; Papadimitriou-Olivgeris, Matthaios; Spiliopoulou, Anastasia; Drougka, Eleanna; Jelastopulu, Eleni; Anastassiou, Evangelos D.; Spiliopoulou, Iris (Frontiers in Microbiology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) remains an important cause of nosocomial and community-associated infections due to its ability to produce toxins and evade host’s immune responses. The aim of the present study was to investigate the association of monocytes immune response in terms of cytokines produced after inoculation with different MRSA clones. Thirty-one clinical MRSA strains were selected on the basis of clonal types, agr groups and toxin genes carriage. Isolates were identified as S. aureus by Gram stain, catalase, coagulase production and PCR for nuc gene. The presence of mecA, lukS/lukF-PV (PVL) and tst (TSST-1) genes, as well as, the determination of agr groups (accessory gene regulator) was performed by PCR. Clonality was investigated by means of multi-locus sequence typing (MLST). Peripheral blood mononuclear cells were stimulated with live bacterial cells for 45 min at a ratio of 1:10. Cells were incubated for 10 hours and supernatants were collected. The levels of Tumor Necrosis Factor alpha (TNFa), IL-1b, IL-8, IL-6, IL-12p40, IL-10, interferon-gamma and IL-2, were measured by Human Cytokine Multiplex Immunoassay kit. Thirteen strains were tst and 12 lukS/lukF-PV-positive. Seven strains belonged to ST80 and ST225, five to ST30 and ST239, while the remaining seven isolates were grouped together as “other”. Strains belonging to ST80 induced statistically lower levels of TNFa, IL-1b, IL-8, IL-6, IL-10, interferon-gamma and IL-2. PVL-positive strains classified into ST80 clone induced statistically lower concentrations of most cytokines as compared to PVL-positive strains belonging to other clones, tst-positive strains and toxin-negative ones. Strains of agr3 group belonging to ST80 induced statistically lower concentrations of most tested cytokines as compared to agr3 strains not-belonging to ST80, agr2 or agr1. This low induction of immune response by MRSA ST80 cannot be attributed to the presence of neither lukS/lukF-PV nor agr3.